2009
DOI: 10.1186/1742-4690-6-42
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 triggering exerts contrasting effects with regard to HIV-1 infection of human dendritic cells and subsequent virus transfer to CD4+T cells

Abstract: Background: Recognition of microbial products through Toll-like receptors (TLRs) initiates inflammatory responses orchestrated by innate immune cells such as dendritic cells (DCs). As these cells are patrolling mucosal surfaces, a portal of entry for various pathogens including human immunodeficiency virus type-1 (HIV-1), we investigated the impact of TLR stimulation on productive HIV-1 infection of DCs and viral spreading to CD4 + T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 94 publications
6
52
0
1
Order By: Relevance
“…This indicates that NR signaling, in addition to directly repressing virus expression in infected cells, is capable of dampening the proinflammatory cytokine response that activates HIV-1 expression in an autocrine or paracrine fashion. , it is not surprising that a number of TLR ligands activate HIV-1 expression in immune cells (3,11,34,36,114,145,161). In agreement with other reports (3,11,36,98,114,145,161), we show that signaling through TLR2 activates HIV-1 expression in macrophages and DCs ( Fig.…”
Section: Nr Ligands Inhibit Hiv-1 Replication In Primary Macrophagessupporting
confidence: 81%
See 1 more Smart Citation
“…This indicates that NR signaling, in addition to directly repressing virus expression in infected cells, is capable of dampening the proinflammatory cytokine response that activates HIV-1 expression in an autocrine or paracrine fashion. , it is not surprising that a number of TLR ligands activate HIV-1 expression in immune cells (3,11,34,36,114,145,161). In agreement with other reports (3,11,36,98,114,145,161), we show that signaling through TLR2 activates HIV-1 expression in macrophages and DCs ( Fig.…”
Section: Nr Ligands Inhibit Hiv-1 Replication In Primary Macrophagessupporting
confidence: 81%
“…Second, STIs cause inflammation that leads to the recruitment of immune cells to the site of inflammation, thereby increasing the size of the HIV-1 target cell population (88,128,136). Third, STIs promote a favorable local environment for HIV-1 replication both by directly activating HIV-1 target cells and by inducing the release of cytokines that favor virus replication through the engagement of Toll-like receptors (TLRs) and other innate immune sensors in cells present in the mucosa (9,10,37,57,75,122,134,145,146,161).…”
mentioning
confidence: 99%
“…24 Additionally, it has also been reported that coculture of DCs and CD4 + T cells increases HIV-1 transmission through TLR2 stimulation. 25 In HIV-1-infected patients, several alterations of TLR expression have been documented 23,[26][27][28][29] raising the possibility that during chronic infection proinflammatory signals can further augment HIV-1 genome expression. The expression and functions of TLRs have been extensively studied in cells from HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…The best-characterized class of these receptors is the family of Toll-like receptors (TLRs) that, upon recognition of conserved microbial-associated molecular patterns (MAMPs), trigger a cascade of signaling events that modulate both the adaptive and innate immune responses (19). TLR activation modulates HIV-1 infection and/or transmission, and, depending on the specific TLR agonist and the target cell, TLR activation can either promote or inhibit HIV-1 expression in vitro (17,18,(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%